Oman through British eyes : British travel writing on Oman from 1800 to 1970 - Hajri, Hilal al- (University of Warwick, 2003)
This thesis focuses on the images of Oman in British travel writing from 1800 to 1970. In texts that vary from travel accounts to sailors’ memoirs, complete travelogues, autobiographies, and letters, it looks at British representations of Oman as a place, people, and culture. It argues that these writings are heterogeneous and discontinuous throughout the periods under consideration. Offering diverse voices from British travellers, this thesis challenges Edward Said’s project in Orientalism (1978) which looks to Western discourse on the Middle East homogenisingly as Eurocentric and hostile. Chapter one explores and discusses the current Orientalist debate suggesting alternatives to the dilemma of Orientalism and providing a framework for the arguments in the ensuing chapters. Chapter two outlines the historical Omani-British relations, and examines the travel accounts and memoirs written by several British merchants and sailors who stopped in Muscat and other Omani coastal cities during their route from Britain to India and vice versa in the nineteenth century. Chapter three is concerned with the works of travellers who penetrated the Interior of Oman. James Wellsted’s Travels in Arabia (1838), Samuel Miles’ The Countries and Tribes of the Persian Gulf (1919) and other uncollected travel accounts, and Bertram Thomas’s Alarms and Excursions (1932) are investigated in this chapter. Chapter four considers the travellers who explored Dhofar in the southern Oman and the Ruba Al-Khali or the Empty Quarter. Precisely, it is devoted to Bertram Thomas’s Arabia Felix (1932) and Wilfred Thesiger’s Arabian Sands (1959). Chapter five looks at the last generation of British travellers who were in Oman from 1950 to 1970 employed either by oil companies or the Sultan Said bin Taimur. It explores Edward Henderson’s Arabian Destiny (1988), David Gwynne-James’s Letters from Oman (2001), and Ian Skeet’s Muscat and Oman (1974). This thesis concludes with final remarks on British travel writing on Oman and recommendations for future studies related to the subject. The gap of knowledge that this thesis undertakes to fill is that most of the texts under discussion have not been studied in any context.
Keywords: Récits de voyage -- Oman

Madkhal ilà Adab al-Riḥlāt fī ʿUmān. Dirāsa Waṣfiyya li’l-Raḥḥāla al-Brīṭāniyyīn, 1626-1970 - Hajri, Hilal al- (نزوى: مجلة فصلية ثقافية, 2003)
Keywords: Récits de voyage -- Oman

Une nouvelle description de Ṣuḥār (ʿUmān) extraite d'un manuscrit inexploité du Kitāb Ṣuwar al-Aqālīm d'al-Iṣṭaḫrī - Ducène, Jean-Charles (Arabica, 2003)
Keywords: Récits de voyage -- Oman

Tārīkh ʿUmān fī Kitābāt baʿḍ al-Raḥḥāla al-Muslimīn - Saʿd Allāh, Abū ‘l-Qāsim (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2003)
Keywords: Récits de voyage -- Oman